Analisis Hukum Islam dalam Transaksi Layanan Pesan Antar Makanan Online: Studi Kasus pada GoFood - Al-Fatih, Muhammad Faras; Shidqi, Muhammad Azam (Department of Islamic Economics Law, 2024)
This research aims to determine Islamic law in online food delivery service transactions on GoFood delivery services and to assess the effectiveness of contracts in GoFood delivery service transactions. (1) Observation, interviews, and documentation are all used in this research as quantitative data collection methods. In the GoFood delivery service, 8 informants in total participated in this research consisting of 3 merchants, 2 drivers and 3 consumers. used random sampling and sampling approaches to identify informants. Based on the research findings, (1) the practice of using contracts in delivery service transactions using Islamic contracts by identifying the relationship between the parties who carry out relationships and transactions in the GoFood delivery service, apart from that it also sharpens the views of contemporary jurisprudence scholars who are pro and Contradictions regarding transactions on the GoFood delivery service, (2) Looking at the Islamic legal perspective on this delivery service transaction by looking at the arguments and views of experts to be able to determine whether or not GoFood delivery service transactions are permissible.